The correlates of inadequate prenatal care of ever-married females from selected regions in the Philippines - Batac, Maria Christina Filomena R.
This study sought to estimate the prevalence of inadequate prenatal care in the Philippines, as well as to elucidate the correlates of inadequate prenatal care utilization of ever-married Filipino women from selected regions of the Philippines. Inadequate prenatal care was defined as initiation of prenatal care later than first trimester or third month of pregnancy and/or reception of less than three prenatal care visits. Among the factors of prenatal care utilization investigated in the study were: 1) maternal socio-demographic factors such as age, place of residence (urban/rural, region), educational attainment, occupation and religion; 2) obstetric factors such as gravidity, parity, history of stillbirth, and fetal loss and experience of danger signs and symptoms during index pregnancy, 3) partner factors such as educational attainment and occupation, 4) social support, 5) perception of gender status, and 6) presence of community-based intervention. A cross-sectional study was utilized involving 3349 ever-married female respondents from various regions of the Philippines, who had experienced a live-birth two years prior to the interview. The prevalence of inadequate prenatal care was found to be 62% (95% CI: 60%-63%). After carrying out multiple logistic regression analysis, inadequate prenatal care was found to be associated with ever-married females who lived in CAR, reached only the high school level, Muslim, had four or more children, had no hypertension during index pregnancy, and were married or living-in with spouses who had low educational attainment and were not white-collar workers. No effect measure modifiers were identified. Gravidity confounded the association between parity and inadequate prenatal care. Knowing the benefits of early and adequate prenatal care, this investigation on the profile of women who did not seek or cannot receive adequate prenatal care provided findings that may help in the development of service adequate prenatal care provided findings that may help in the development of service delivery strategies focused on the groups likely to obtain inadequate prenatal care.